A finite element study on three maxillary protraction devices for treating maxillary sagittal hypoplasia at different levels of bone fusion - Sun, Kaiyuan; Zhao, Gang; Jin, Yinan; Tang, Bowen; Liu, Yufei; Wang, Lu (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveThis study utilized three-dimensional finite element analysis to assess stress distribution in the maxilla and sutures, as well as craniofacial bone and tooth displacement, in patients exhibiting mild to moderate sutural fusion when using three distinct maxillary protraction devices.MethodsA craniofacial composite model with mild to moderate sutural fusion was constructed and fitted with three types of appliances: a tooth-supported maxillary protraction device, a micro-implant maxillary protraction device, and an invisible aligner maxillary protraction device. A traction force was applied at a 30° forward-downward angle relative to the occlusal plane. The equivalent elastic strain conditions of the maxilla and suture lines were compared and analyzed, along with craniofacial bone and tooth displacement under various loading conditions.ResultsStress distribution in the sutures during maxillary protraction varied among the three appliance types. The micro-implant group exhibited the highest equivalent strain in the frontal-maxillary and naso-maxillary sutures, while the zygomatic-temporal suture experienced the greatest strain in the clear aligner group. Under the same level of suture fusion, the clear aligner group displayed the most significant maxillary displacement and incisor labial inclination, in contrast to the micro-implant group, which showed the least incisor labial inclination. As sutural fusion increased, both the stress on the sutures and the extent of skeletal displacement significantly decreased, while the propensity for maxillary rotation increased.ConclusionEach of the three appliance types effectively facilitates maxillary advancement, though they result in varying degrees of incisor labial inclination. The osteogenic effect of maxillary protraction diminishes with increased sutural fusion. The micro-implant maxillary protraction appliance is advisable for patients with nasal root depression, while the clear aligner variant is preferable for those with midface depression. Furthermore, in patients with advanced sutural fusion, it is crucial to adjust the traction direction to mitigate undesirable maxillary rotation.